Biometric characteristics of watermelon plants - Zokirov Kurbonalijon; Ergashova Durdona; Yuldasheva Roila; Komilov Akhmadjon; Kadirova Dilbar; Abdullayev Dadaxon (BIO Web of Conferences)
Changing the level of mineral nutrition has a greater effect on increasing the length of the main shoot and the total length of shoots than the sowing patterns used. With all sowing patterns, with an increase in the fertilizer dose to N120P100K50 kg/ha, the length of the main shoot increases. In dense crops, the biomass of fruits increased more intensively. Most of their weight is formed by the time of the first harvest. It should be noted that for all variants, a significant part of the total dry mass is created during the period of fruit formation and, mainly, due to their growth. With a change in the sowing pattern towards thickening plants in a row to 40 cm, the number of plants per ha increases. Consequently, this leads to an increase in the total mass of plants per ha. The results of the conducted surveys showed that, when converted to hectare, the total weight of absolutely dry mass of plants in all periods of growth increased with an increase in the density of watermelon plants per ha.